KONSENTRASI ASAM FOSFAT (H3PO4 ) TERHADAP KARAKTERISTIK ARANG AKTIF DARI TEMPURUNG BUAH NIPAH - Saitun; Usman Pato; Yelmira Zalfiatri (Fakultas Pertanian Universitas Riau, 2024)
This study aims to obtain selected characteristics of activated charcoal made from Nypa fruitcans shell with the help of phosphoric acid as an activator. This study was conducted using a completely randomized design (CRD) with four treatments and four replications. The treatments in this study used some concentration of phosphoric acid namely; H3PO4 7.5%, H3PO410%, H3PO4 12.5%, and H3PO4 15%. Parameters observe were the yield, moisture, ash, volatile matter and pure carbon contents as well as iodine absorption. The data obtained were analyzed statistically using statistical software IBM SPSS version 23 with an analysis of variance (ANOVA) test, if F count ≥ F table and continued with Duncan’s multiple range test (DMRT) at level 5%. The results showed that increasing the concentration of phosphoric acid used significantly affected all parameters on the activated charcoal. Activated charcoal with the best treatment was found in the N4 treatment with a yield 77.78%, moisture content 3.80%, ash content 6.86%, volatile matter content 7.48%, pure carbon content 81.86% and absorption of iodine of 869.27 mg/g.